Penyuluhan tentang Keputihan pada Remaja Putri di Pondok Pesantren Tahfidz Qur’an Hisbah Al-Fatih Sintang - Arum Seftiani Lestari; Dian Ika Pratiwi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Adolescence is a developmental phase and transition period from childhood to adulthood that is characterized by accelerated physical, mental, emotional, and social changes. This development begins with growth, change, and the emergence of various opportunities and risks of problems in reproductive health. Adolescents must prepare themselves from the aspect of knowledge and attitudes toward achieving healthy reproduction. One of the reproductive health problems in adolescent girls is vaginal discharge. The impact of abnormal vaginal discharge is the occurrence of infection and can lead to infertility. The purpose of this counseling is to provide health education about vaginal discharge so that the knowledge of young women increases so that they can better understand how to prevent vaginal discharge and maintain the cleanliness of the reproductive organs. The counseling was carried out at the Tahfidz Qur'an Islamic Boarding School Hisbah Al Fatih Sintang with 16 participants. Counseling is done using lecture and question and answer methods, the media used are leaflets and PowerPoint slide shows. The measurement of participants' knowledge was carried out by conducting a pretest and posttest and processed by the Paired Sample Test. The test results show that there is a change in the level of knowledge before and after being given counseling with a Sig value. (2-tailed) of 0.000 < 0.05. The conclusion from the counseling was that there was an increase in participants' knowledge after given counseling. Counseling participants are expected to be able to apply a clean and healthy lifestyle to avoid vaginal discharge.